Effect of Duration and Onset of Clinical Signs on Short-Term Outcome of Dogs with Hansen Type I Thoracolumbar Intervertebral Disc Extrusion - Upchurch, David A.; Renberg, Walter C.; Turner, Hannah S.; McLellan, Jiena G. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to determine if either the rate of onset of clinical signs or duration from initial clinical signs to surgical decompression affected the overall quality or duration of recovery in dogs with intervertebral disc extrusion.Study Design This was a retrospective case series of 131 client owned dogs. Medical records of dogs surgically treated with hemilaminectomy for intervertebral disc extrusion between January 2016 and December 2017 were reviewed for signalment, neurological grade at presentation, rate of onset and duration of clinical signs and surgical variables. These variables were analysed to determine their effect on return of pain sensation, urinary continence and ambulation.Results Duration of clinical signs prior to surgery and rate of onset of signs did not correlate with return of pain sensation, urinary continence or ambulation. Preoperative neurological grade was the main variable that was found to be associated with outcome.Conclusions Delay from initial clinical signs of intervertebral disc extrusion to surgery is unlikely to affect the ultimate outcome or the length of time for a dog to regain pain sensation, urinary continence or ambulation. The rate of onset of signs likewise does not influence these outcomes.
Keywords: intervertebral disc extrusion; dog; hemilaminectomy; outcome; surgical timing